Pengaruh Minat Masyarakat Aceh terhadap Keputusan Memilih Produk Perbankan Syariah di Kota Banda Aceh - Rahmah Yulianti (Jurnal Dinamika Akuntansi dan Bisnis, 2015)
The objective of this study is to examine the influence the decision to select product Islamic bank, they were because, religious motivation, and service quality. The data were collected by questionnaire as the instrument. The questionnaires were distributed to 100 respondents as the active customers of sharia bank in Banda Aceh. The data were analyzed by validity and reliability test to evaluate the questionnaire and by linier regression to evaluate the influential factors of those variables. The result showed that religious motives and service quality positively influenced the decision to choose product Islamic Bank.The objective of this study is to examine the influence the decision to select product Islamic bank, they were because, religious motivation, and service quality. The data were collected by questionnaire as the instrument. The questionnaires were distributed to 100 respondents as the active customers of sharia bank in Banda Aceh. The data were analyzed by validity and reliability test to evaluate the questionnaire and by linier regression to evaluate the influential factors of those variables. The result showed that religious motives and service quality positively influenced the decision to choose product Islamic Bank.